2021
DOI: 10.1080/0158037x.2021.1883577
|View full text |Cite
|
Sign up to set email alerts
|

Professional learning in healthcare settings in resource-limited environments: what are the tensions for professionals’ knowing and learning about antimicrobial resistance?

Abstract: This article examines tensions that professionals in healthcare settings in low-to-middle income countries (LMICs) face in the evolving field around surveillance of antimicrobial resistance (AMR). Few public health problems are of greater global importance today than AMR, that poses a threat to our ability to treat infections. In this context, the microbiology laboratory occupies a prominent place and the knowledge field of microbiology is expanding. In this study, we interviewed twentythree (n = 23) professio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…lack of consideration of long-term outcomes) and influences of capitalism that promote ‘perverse antimicrobial prescription’ without thorough assessment of need. 35 , 36 Additionally, a 2014 situational analysis of India by Madhok et al . 6 found that ‘reporting of incidents related to patient safety is seen as an act of complaining’, which ‘discourages reporting or owning mistakes’.…”
Section: Discussionmentioning
confidence: 99%
“…lack of consideration of long-term outcomes) and influences of capitalism that promote ‘perverse antimicrobial prescription’ without thorough assessment of need. 35 , 36 Additionally, a 2014 situational analysis of India by Madhok et al . 6 found that ‘reporting of incidents related to patient safety is seen as an act of complaining’, which ‘discourages reporting or owning mistakes’.…”
Section: Discussionmentioning
confidence: 99%
“…At the local level, there are insufficient protocols to enable cross-sectoral collaboration and information sharing across different professions. This was raised as a significant challenge, fundamental to the reduction of AMR (Sayed et al, 2018;Charitonos and Littlejohn, 2021). Similar concerns were raised in connection with national-level collaboration.…”
Section: Discussionmentioning
confidence: 93%
“…Recent work by Singh and Manchada (2017) identified following challenges: limited diagnostic capability of laboratories; low numbers of trained professionals trained; poor collaboration across different parts of the health system; and insufficient policy legislation to ensure high-quality surveillance data. Other studies have identified challenges around actions of raising the awareness of AMR, and emphasizing the importance of improved infrastructure, information and regulation (Pearson and Chandler, 2019); limited levels of communication between local clinics and central or national laboratories (Sayed et al, 2018); rigid structures and rules in workplace settings that hinder new AMR surveillance practice (Charitonos and Littlejohn, 2021); issues associated with hierarchies in health care (Gebretekle et al, 2018) leading to issues of trust among clinicians and lab workers (Charitonos and Littlejohn, 2021); and problems caused by the practices of clinicians who do not draw on the expertise of other specialists, such as nurses or pharmacists (Charani et al, 2019).…”
mentioning
confidence: 99%
“…in primary care (NHS, 2019)? A related question then, might be in how the expansive facets of learning are born: from changes in the range of professionals involved, in their divisions of labour/job descriptions, repertoires of actions/action sequences, and sites of work established in the unfolding of larger projects of change (Charitonos & Littlejohn, 2021); which empirical data are reflective of key ideas in these 'master conceptual schemes' (Merton, 1968) on offer for example, in considering the routine, dynamic, or expansive ingredients of change?…”
Section: In Conversation With Academic Pasts and Presentmentioning
confidence: 99%